Anti-cancer compound screening identifies Aurora Kinase A inhibition as a means to favor CRISPR/Cas9 gene correction over knock-out - Danny Wilbie; Selma Eising; Vicky Amo-Addae; Johanna Walther; Esmeralda Bosman; Zhiyong Lei; Olivier G de Jong; Jan J Molenaar; Enrico Mastrobattista (PLoS ONE, 2025)
CRISPR gene therapy holds the potential to cure a variety of genetic diseases by causing a targeted DNA break, which is repaired by host DNA damage responses. One option to introduce precise gene corrections is via the homology-directed repair (HDR) pathway. The problem in utilizing this pathway is that CRISPR-induced double stranded DNA breaks are more likely to be erroneously repaired by the non-homologous end joining (NHEJ) pathway, which may introduce random insertions or deletions at the cut site. We screened a small library of oncological drug compounds to steer the DNA repair process towards preferential HDR activation. We included forty compounds in the screen based on their mechanism of action. After optimizing the toxicity and adding these compounds during gene editing, nine showed a potential benefit for HDR activation. Three were shown to be beneficial after validation: rucaparib, belinostat and alisertib. The Aurora Kinase A inhibitor alisertib in particular led to an over 4-fold increase in preferential gene correction over gene knock-out in two cell models (HEK293T and Hepa 1–6) at sub-micromolar dosages on the eGFP locus, prompting further validation. On the long term this pathway did show cytotoxicity especially in the HEK293T cells, indicating further mechanistic investigation is needed, but this toxicity was less pronounced in primary hepatocytes.